On the Comparative Stability of Li and Na Metal Anode Interfaces in Conventional Alkyl Carbonate Electrolytes. Issue 13 (1st January 2015) - Iermakova, D. I.; Dugas, R.; Palacín, M. R.; Ponrouch, A.
Abstract : A comparative study of the electrode/electrolyte interface was carried out for lithium and sodium metal anodes in electrolytes consisting in 1 M LiPF6 in EC0.5 :DMC0.5 (LP30) and 1 M NaPF6 in both EC0.5 :DMC0.5 and EC0.45 PC0.45 DMC0.1 . Symmetric Li/Li cells exhibited low polarization and smooth charge discharge curves with current densities of 0.1 and 1 mA/cm 2 . In contrast, large overpotentials were observed even at 0.1 mA/cm 2 for Na/Na cells. Such differences cannot be related to ionic conductivity of the electrolytes but are rather due to an enhanced interfacial resistance (Rct + RSEI ) as deduced from impedance measurements. The composition of the SEI layer was investigated by FTIR and found to be stable for Li electrodes but to evolve upon cycling for Na electrodes which is also in agreement with differences in surface morphology detected by SEM. A lower stability (partial solubility) of the SEI would also enable to understand the differences in the impedance of identical hard carbon (HC) electrodes in cells with either Li or Na counterelectrodes. These results cast some concerns on the reliability of the so termed half cell characterization and call for caution when interpreting the results of potential electrode materials for sodium ion batteries.